Engineering the optical properties of silicon using sub-wavelength structures - Halir, Robert; Ortega-Moñux, Alejandro; Maese-Novo, Alejandro; Pérez-Galacho, Diego; Zavargo-Peche, Luis; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo; Cheben, Pavel; Schmid, Jens H.; Xu, Dan-Xia; Janz, Siegfried; Fedeli, Jean-Marc (IEEE Photonics Society, 2013)
In most integrated optics platforms, including silicon-on-insulator, only minor modifications in refractive index are possible. The geometry of the waveguiding structure is thus the only degree of freedom for the design of devices. The use of sub-wavelength gratings (SWGs), i.e. structures that are small enough to suppress diffraction effects, enables local engineering of both refractive index and dispersion, thereby opening new possibilities for device design. Here we present some of the recent advances in refractive index and dispersion engineering using silicon SWGs, focussing on ultra-broadband and compact multimode interference couplers and directional couplers
Keywords: Óptica integrada - Congresos; Fotónica - Congresos; Integrated optics; Silicon photonics; Subwavelength structures; Dispersion engineering